Effects of soy isoflavones extract on the lipid profile and uterus in ovariectomized rats. (1st February 2021) - Fonseca, Caio Cesar Navarrete da; Cezar, Luana Carvalho; Franco, Paulo Celso; Simões, Ricardo Santos; Sasso, Gisela Rodrigues da Silva; Simões, Manuel de Jesus; Florencio-Silva, Rinaldo
Abstract: Aim: Although soy isoflavones (ISO) have been shown to relief postmenopausal symptoms, it remains inconclusive whether ISO can improve lipid-profile without uterotrophic effects under estrogen-deficiency. Thus, we investigated the effects of ISO on lipid-profile and uterus of ovariectomized (Ovx) rats. Materials and methods: Twenty-five adult rats were Ovx or Sham-operated (Sham) and assigned into five groups: Sham and Ovx groups, administered with vehicle solutions; Ovx-E, treated with 10 µg/kg of 17β-Estradiol; Ovx-ISO, treated with 200 mg/kg of ISO; Ovx-E + ISO, treated with estradiol + ISO combined. After fifty days of treatments, rats were euthanized and uterine horns were processed for histomorphometry or to collagen fibers and glycosaminoglycans evaluations. Blood samples were collected to evaluate levels of triglycerides, total cholesterol (TC) and its fractions (HDL/VLDL). Data were subjected to statistical analysis ( p  < .05). Results: Uterus weight was lower in Ovx group than the Sham and Ovx-E groups, whereas it was similar between Ovx and Ovx-ISO groups. Histomorphometry showed atrophic uterus in Ovx and Ovx-ISO groups, whereas uterotrophic effects were noticed in Ovx-E and Ovx-E + ISO groups. Collagen fibers-birefringence was higher in Sham, Ovx, and Ovx-ISO groups than in Ovx-E and Ovx-E + ISO groups. Sulfated glycosaminoglycans content was similar among Sham, Ovx, and Ovx-ISO groups, while it was higher in estrogen-treated groups; total glycosaminoglycans content was similar among groups. TC and HDL was higher in Ovx-ISO group, whereas VLDL and triglycerides levels was higher in Ovx-E + ISO group and similar among other groups. Conclusion: Soy isoflavones at 200 mg/kg have slight beneficial effects on lipid-profile without uterotrophic effects in Ovx rats.